Israel, a journey of light. 2, A Jewish hope - Tweedie, J. (John); Christians for Israel Canada; One Media (Firm); Exploration Films (Firm) ([United States] : Exploration Films Distribution, 2010)
Rev. Dr. John Tweedie explores how Jesus and Saul became instrumental in rekindling the flame of individual hope amid the pagan darkness of Roman rule over Israel. Learn how the concept of a 'messiah' or 'Christ' figure developed in the ancient world and how Salvation, as Christians understand it today, is yet another gift that came to the world through the Jewish people.
DVD, all regions, widescreen (16:9); Dolby Digital.
Host, John Tweedie.
Rating: Not rated.
Keywords: Israel -- History; Israel -- Church history; Documentary films; Nonfiction films; Religious films; Historical films